Age-Period-Cohort Analysis of Type 2 Diabetes Mortality Attributable to Particulate Matter Pollution in China and the U.S. - Xiaoxue Liu; Maigeng Zhou; Chuanhua Yu; Zhi-Jiang Zhang (Journal of Diabetes Research)
Aim. We aimed to assess and compare secular trends in type 2 diabetes mortality attributable to particulate matter pollution in China and U.S. Methods. We performed an age-period-cohort (APC) analysis to estimate the independent effects of age, period, and cohort on mortality of type 2 diabetes attributable to particulate matter pollution. We collected age-standardized and age-specific mortality rates (1990-2017) from the Global Burden of Disease 2017 Study for China and the U.S. Results. During the period 1990-2017, the age-standardized mortality rates of type 2 diabetes attributable to particulate matter pollution in China showed a general increasing trend, while that in U.S. showed an increase before 2002 and subsequently a decrease. The age effect increased markedly in China compared with the U.S. The period effect showed a substantially increase in China while that in the U.S. increased during 1990-2007 and tended to be stable during 2007-2017. The cohort effect peaked in birth cohort born in 1902–1906 in both China and U.S. and declined consistently in the cohort born in 1992-1996. Conclusions. The age-standardized mortality rates of type 2 diabetes attributable to particulate matter pollution, the age, and period effect in China have been increasing in both sexes from 1990 to 2017. The overall mortality in the U.S. began to decrease since 2003, and the period effect showed a tendency to stabilize. Consequently, it is necessary to educate the nation with the correct knowledge and adopting policies on pollutant emission and techniques to reduce air pollution in China.